Revisiting Coffee Shops as Public Space in Purwokerto - Aidatul Chusna; Arizal Mutahir; Muhammad Taufiqurrohman (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2021)
The increasing number of coffee shops identifies the dynamics of urban life in Purwokerto. However, how does the existence of these coffee shops influence the socio-cultural life of the society?  The research aims to examine the socio-cultural functions of coffee shops in Purwokerto in accordance to the role of public sphere. The concept of public sphere by Jurgen Habermas is used the theoretical foundation of the analysis. Using descriptive qualitative method, the study analyses data taken from the observation and interview process. Due to the large number of coffee shops in Purwokerto, the researchers select six coffee shops with different characteristics. The research finds that coffee shops in Purwokerto tend to be a place to meet up after school or work and spend their leisure time, as the coffee shop offers a good atmosphere to be more focused and productive on their work. Thus, the function of public sphere is hardly found. Instead, coffee shop becomes a private place for individuals to engage with their own individuality and communities